Analisis Pelaksanaan Program Tanggap Darurat Kebakaran di Suku Dinas Penanggulangan Kebakaran dan Penyelamatan Kotamadya Jakarta Timur Tahun 2021: Analysis of the Implementation of the Fire Emergency Response Program in the East Jakarta Municipal Fire Handling and Rescue Sub-Department in 2021 - Camelia (MPI Press, 2023)
Background: Fire is a fire that cannot be controlled, meaning that it is beyond human ability and desire. Fire hazard is a hazard caused by a potential threat and degree of exposure to flames starting from the start of the fire to the spread of the fire, smoke and gas produced. Objective: To understand and also know the management of fire emergency response management at the East Jakarta City Fire and Rescue Service. Method: This research uses qualitative research with an observational approach. Primary data sources were collected through interviews and direct field observations. Secondary data was obtained from the fire emergency system literature as well as supporting data on the general description of the fire emergency program for the East Jakarta City Fire Department. Results: The East Jakarta City Fire and Rescue Service has a fire protection system, emergency response procedures in the event of a fire, technical guidelines for emergency action plans in the event of a fire and an organization/emergency response team. For fires, the East Jakarta City Fire and Rescue Service already have an active fire protection system in the form of a fire detection system and a fire extinguishing system. Conclusion: The East Jakarta City Fire and Rescue Service have fulfilled almost all the criteria for a passive fire protection system, namely the availability of hydrants around the building and canals for fire barriers with the following conditions: Active Protection System for fire detectors that function properly, fire alarms that function properly well, sprinklers that work properly, several fire extinguishers don’t work and are outside the cabinet and hydrants that don't work. Passive emergency door protection system that is not functioning properly, there is no emergency lighting system, the fire ladder is not functioning, there are no directional signs and there are means of self-evacuation.